Trees in trimmed hedgerows but not tree health increase diversity of oribatid mite communities in intensively managed agricultural land. (November 2019) - Spaans, Florentine; Caruso, Tancredi; Hammer, Edith C.; Montgomery, Ian
Abstract: Hedgerows structure agricultural landscape worldwide but little is known on their soil communities. In the intensively managed agricultural landscapes of Ireland and the UK, hedgerows protect soil from degradation and are thought to provide a reservoir of soil biodiversity for the farmed fields. But hedgerows are currently threatened by emergent tree diseases spread with rising volumes of trade in plants. This study analysed the effect of the most dominant hedgerow tree species on the composition and diversity of soil communities, which we estimated with oribatid mites in the context of an imminent ash dieback outbreak in Northern Ireland. We hypothesised that the environmental heterogeneity created by different tree species and good tree health are beneficial to the abundance and diversity of these soil communities. We found that communities differ, both in terms of species composition and relative abundances, between different trees in the trimmed hedgerows, and between untrimmed and trimmed hedgerows. The presence of trees was associated with more variable species composition. The analysis of phospholipid fatty acids (PLFA) showed that pasture and adjacent hedgerows were dominated by bacteria but there was no clear relationship between bacterial biomass and oribatid abundance or richness. However, changes in bacterial PLFAs were correlated positively with changes in oribatid community composition. Soil under ash trees which were diseased supported a higher species richness and greater abundance of oribatids than healthy trees. We conclude that the presence of different tree species in hedgerows adds to the overall diversity of soil hedgerow communities and hypothesise that the structural heterogeneity created by tree canopy drives increased diversity. Ill health in ash trees is currently positively affecting oribatid communities, possibly due to the temporarily increase in organic matter in soil. The epidemic of ash dieback, however, is expected to kill and remove trees in the medium term and so reduce soil community diversity in the long term. Highlights: Hedgerows host significant soil oribatid mite biodiversity. Trimmed hedgerows and tree standards have distinct species composition. The presence of trees in trimmed hedgerows increases biodiversity. The positive short term effects of diseased tree may reverse in the long term.